2021
DOI: 10.1002/ange.202105166
|View full text |Cite
|
Sign up to set email alerts
|

Auf zur Wasserstoffentwicklung: Das Infrarot‐Spektrum von hydratisiertem Aluminiumhydrid‐Hydroxid HAlOH+(H2O)n−1, n=9–14

Abstract: Diese Autoren haben zu gleichen Teilen zu der Arbeit beigetragen.Hintergrundinformationen und Identifikationsnummern (ORCIDs) der Autoren sind unter:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…In the case of Al + (H 2 O) n , H/D exchange experiments with D 2 O indicate that larger clusters are indeed present as HAlOH + (H 2 O) n-1 , but for n > 40, the exchange ceases, [16] leaving the question open whether these clusters resume the Al + (H 2 O) n structure or the H/D exchange reaction, which requires efficient proton transfer, [17] becomes hindered. Our recent infrared spectroscopic study confirmed the presence of the HAlOH + (H 2 O) n-1 structure for n = 9-14, [18] corroborating the theoretically predicted mechanism of H 2 formation in these species. [19,20] Around n = 8, the HAlOH + (H 2 O) n-1 structure is formed.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the case of Al + (H 2 O) n , H/D exchange experiments with D 2 O indicate that larger clusters are indeed present as HAlOH + (H 2 O) n-1 , but for n > 40, the exchange ceases, [16] leaving the question open whether these clusters resume the Al + (H 2 O) n structure or the H/D exchange reaction, which requires efficient proton transfer, [17] becomes hindered. Our recent infrared spectroscopic study confirmed the presence of the HAlOH + (H 2 O) n-1 structure for n = 9-14, [18] corroborating the theoretically predicted mechanism of H 2 formation in these species. [19,20] Around n = 8, the HAlOH + (H 2 O) n-1 structure is formed.…”
Section: Introductionsupporting
confidence: 86%
“…It is well established that Al + (H 2 O) n rearranges to HAlOH + (H 2 O) n-1 , and we observe the AlÀ H stretching mode in our infrared spectra in traces for n = 4, with quickly increasing intensity for larger clusters. [18] The inserted structure HAlOH + (H 2 O) n-1 does not absorb UV light with λ � 225 nm for n = 2-4, and hydration does not seem to lead to an appreciable redshift. We therefore assign the size-dependence of the absorption cross-section and the disappearance of the absorption to the presence of the HAlOH + (H 2 O) n-1 structure.…”
Section: Photodissociation Of Al + (H 2 O) N N >mentioning
confidence: 99%